Clonal lineage from normal endometrium to ovarian clear cell carcinoma through ovarian endometriosis. Issue 8 (26th June 2020) - Suda, Kazuaki; Cruz Diaz, Luis Antonio; Yoshihara, Kosuke; Nakaoka, Hirofumi; Yachida, Nozomi; Motoyama, Teiichi; Inoue, Ituro; Enomoto, Takayuki
Abstract: Clear cell carcinoma of the ovary is thought to arise from endometriosis. In addition, retrograde menstruation of shed endometrium is considered the origin of endometriosis. However, little evidence supports cellular continuity from uterine endometrium to clear cell carcinoma through endometriosis at the genomic level. Here, we performed multiregional whole‐exome sequencing to clarify clonal relationships among uterine endometrium, ovarian endometriosis and ovarian clear cell carcinoma in a 56‐year‐old patient. Many somatic mutations including cancer‐associated gene mutations in ARID1A, ATM, CDH4, NRAS and PIK3CA were shared among epithelium samples from uterine endometrium, endometriotic lesions distant from and adjacent to the carcinoma, and the carcinoma. The mutant allele frequencies of shared mutations increased from uterine endometrium to distant endometriosis, adjacent endometriosis, and carcinoma. Although a splice site mutation of ARID1A was shared among the four epithelium samples, a frameshift insertion in ARID1A was shared by adjacent endometriosis and carcinoma samples, suggesting that the biallelic mutations triggered malignant transformation. Somatic copy number alterations, including loss of heterozygosity events at PIK3CA and ATM, were identified only in adjacent endometriosis and carcinoma, suggesting that mutant allele‐specific imbalance is another key factor driving malignant transformation. By reconstructing a clonal evolution tree based on the somatic mutations, we showed that the epithelium samples were derived from a single ancestral clone. Although the study was limited to a single patient, the results from this illustrative case could suggest the possibility that epithelial cells of ovarian endometriosis and clear cell carcinoma were descendants of uterine endometrial epithelium. Abstract : Suda et al performed whole‐exome sequencing for normal endometrial endometrium, two ovarian endometriotic epitheliums that were distant from or contiguous to the carcinoma, and carcinoma. A substantial number of somatic mutations were shared among four epithelium samples, and the mutant allele frequencies of shared mutations increased sequentially from uterine endometrium to carcinoma. Clonal evolution analysis revealed that epithelial cells of ovarian endometriosis and clear cell carcinoma were descendants of uterine endometrial epithelium.